2012
DOI: 10.5194/acpd-12-5851-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling nitrous acid and its impact on ozone and hydroxyl radical during the Texas Air Quality Study 2006

Abstract: Nitrous acid (HONO) mixing ratios for the Houston metropolitan area were simulated with the Community Multiscale Air Quality (CMAQ) model for an episode during the Texas Air Quality Study (TexAQS) II in August/September 2006 and compared to in-situ MC/IC (mist-chamber/ion chromatograph) and long path DOAS (Differential Optical Absorption Spectroscopy) measurements at three different altitudes. Several HONO sources were accounted for in simulations, such as gas phase formation, direct emissions, nitrogen dioxid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Measurements taken during the 2006 Texas Air Quality Study (TexAQS) and the 2009 SHARP campaign showed strong vertical HONO concentration gradients during the day with higher values near the ground, which modeled homogeneous chemistry did not predict (e.g., Czader et al, 2012;Wong et al, 2012). Wong et al (2012) hypothesized that the missing HONO formation pathways are photolytic and occur on or near the ground.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 94%
See 2 more Smart Citations
“…Measurements taken during the 2006 Texas Air Quality Study (TexAQS) and the 2009 SHARP campaign showed strong vertical HONO concentration gradients during the day with higher values near the ground, which modeled homogeneous chemistry did not predict (e.g., Czader et al, 2012;Wong et al, 2012). Wong et al (2012) hypothesized that the missing HONO formation pathways are photolytic and occur on or near the ground.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 94%
“…Several recent modeling studies with CMAQ (e.g., Sarwar et al, 2008;Czader et al, 2012;Gonçalves et al, 2012;Zhang et al, 2012b) and WRF-Chem (e.g., Li et al, 2010Li et al, , 2011Tang et al, 2015) have considered additional mechanisms for HONO formation, and have found improvement in model performance, although the degree of improvement is variable depending upon the approach used. The Supplemental Section provides a brief review of the methods and results from some of these modeling studies.…”
Section: Surface Model For Hono Formation In Camxmentioning
confidence: 97%
See 1 more Smart Citation
“…Another area of active ongoing research has considered elevated daytime HONO concentrations, which cannot be explained by the known homogenous reaction between NO and OH and the sources just mentioned (Acker and M€ oller, 2007;Czader et al, 2012Czader et al, , 2013Li et al, 2012;Qin et al, 2009;Sorgel et al, 2011;Su et al, 2008b;VandenBoer et al, 2013). Several potential photo-enhanced sources have been proposed, including light-dependent heterogeneous reactions of NO 2 on aerosol and ground surfaces, photolysis of HNO 3 absorbed on surfaces, the reaction of excited NO 2 with water vapors and the reaction of NO 2 with HO 2 *H 2 O (Kleffmann, 2007;Li et al, 2008Li et al, , 2014Monge et al, 2010;Wong et al, 2012;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, early modeling studies of the Houston airshed that assumed either direct emissions of formaldehyde from industrial flares [ Vizuete et al ., ] or secondary formation of HONO on surfaces, such as heterogeneous conversion of NO 2 on soot particles [ Lei et al ., ], resulted in significant additions to peak ozone. This has since been confirmed by more contemporary modeling studies [ Olaguer , ; Czader et al ., ]. The regulatory implication of this finding was that the simulated efficacy of control strategies in the Houston SIP was likely to be underestimated in the absence of additional sources of radical precursors, both primary and secondary.…”
Section: Introductionmentioning
confidence: 99%